2012
DOI: 10.1902/jop.2011.110045
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Flap Approach for Surgical Debridement of Deep Intraosseous Defects: A Randomized Controlled Trial

Abstract: The surgical debridement of intraosseous periodontal defects resulted in comparable, substantial CAL gains and PD reductions as well as limited postoperative REC increases when defects were accessed with the SFA or DFA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
90
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(101 citation statements)
references
References 43 publications
7
90
0
4
Order By: Relevance
“…Previous randomized clinical trials have clearly demonstrated that an SFA may optimize clinical outcomes compared with a conventional double‐flap approach when used with 15 or without 9 regenerative devices, while limiting the level of post‐surgery pain and discomfort 15 . Adjunctive use of a CTG unavoidably results in a more technically demanding procedure and increases the intra‐ and postoperative morbidity due to the need for an additional surgical site for graft harvesting.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous randomized clinical trials have clearly demonstrated that an SFA may optimize clinical outcomes compared with a conventional double‐flap approach when used with 15 or without 9 regenerative devices, while limiting the level of post‐surgery pain and discomfort 15 . Adjunctive use of a CTG unavoidably results in a more technically demanding procedure and increases the intra‐ and postoperative morbidity due to the need for an additional surgical site for graft harvesting.…”
Section: Discussionmentioning
confidence: 99%
“…Presurgery and surgical procedures were performed by expert periodontal surgeons (LT, LM, RF, GR) involved in previous clinical trials on SFA 7‐12,15 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations